Knowledge based-system for alternative design, cost estimating and scheduling - Mohamed, A; Celik, T (Elsevier Science Bv, 2002)
The traditional design, cost estimating and scheduling procedures focus on assessing costs and schedule after design decisions are made and conveyed to construction drawings and design that is, they do not have a mechanism that allow the designer to perform a rapid 'what if analysis on design alternatives and cost analysis of different types of building materials and alternative schedule analysis at early stage of project without accompanying of detailed design and drawing. Moreover, the available scheduling tools are not integrated to design and cost estimating system and hence require manual input of activities lists, activities sequencing, resources, costs and durations to generate project schedule and they are unable to consider the effect of productivity factors and the resulting uncertainty inherent in each activity. This paper presents an integrated knowledge based system for construction cost estimating and scheduling. The knowledge based system supports an automated alternative design analysis with on line schematic drawing, material selection, crew selection and productivity analysis for generating activities sequencing, normal durations, productivity adjusted: durations, cost estimate, list of materials selected and their respective quantities and list of assigned crew. An analysis of alternative design, cost estimating and scheduling for a residential building using the integrated system is presented. (C) 2002 Elsevier Science, B.V. All rights reserved.
Keywords: cost estimating; building design; planning and scheduling; productivity; expert system